Impact of Sociodemographic Variables and Clinical Parameters On Outcome of Pediatric Tetanus Patients: A Retrospective Study From an Infectious Disease Hospital in Bangladesh (Journal of Chittagong Medical College Teachers' Association, 2025)
Background: Tetanus is a vaccine-preventable disease with high mortality. It is still a major cause of death in the pediatric age group particularly in developing countries. This study aimed to determine the demographic and clinical profile and their impact on the outcome of tetanus in children.Materials and methods: This retrospective study was conducted at the Bangladesh Institute of Tropical and Infectious Diseases (BITID), Fouzderhat, Chattogram. The medical records of pediatric tetanus patients (age £ 17 years) admitted between January 2014 and December 2021 were retrieved. Data regarding the demographic and clinical profile and final outcome of the patients were noted. The statistical analysis was conducted using SPSS version 25.  Results: There were a total of 81 pediatric tetanus cases during the study period. Male to female ratio was 1.6:1. Most (69.1%) of the patients came from rural areas. Eighteen (22.2%) cases were neonates. The majority of the patients were between 6-10 years of age (28.4%). The median incubation period was 7 days (IQR: 5-10 d, range: 3-12 d). Median age at presentation was 10 days (IQR: 710.25 days) in neonate and 8 years (IQR: 5-11 years) in non-neonatal group. Lockjaw (85.2%) was the commonest presentation, followed by convulsion (80.2%) and then fever (44.4%). About one-fourth (25.9%) of the patients developed complications during the hospital stay. Nearly two-thirds (67%) of mothers of neonatal tetanus cases were not vaccinated against tetanus. Most of the nonneonatal tetanus cases (80.9%) were either partially immunized or unimmunized. Overall in-hospital mortality was 28% and mortality was high among neonates (44.4%). There was a significant increase in mortality among ethnic minority group (p = 0.03) and patients with complications (p=0.02). Recovered patients had a significantly longer duration of hospital stay (Median 19.5 days; IQR: 16–25 days) than those who died (Median 2 days, IQR 1-4 days) (p